Pengaruh Fenomen Global Pacific Decadal Oscillation Dengan Madden-Julian Oscillation Di Provinsi Papua - Nur Rachmi; Achmad Yasir Baeda; Sabaruddin Rahman (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
Tropical areas such as Indonesia are ocean areas that show convective activity responses that affect the global climate balance in space and time. The equatorial region, especially Indonesia, is subject to very complex ocean-atmospheric phenomena which are influenced by many factors and phenomena such as the Monsoon/Tropical Convergence Zone (ITCZ), El Niño Southern Oscillation (ENSO), Madden-Julian Oscillation (MJO), Tropical Cyclone. /Temperate Forcing, Indian Ocean Dipole Mode (IODM), and Pacific Decadal Oscillation (PDO). This journal focuses on discussing two phenomena, namely the Madden-Julian Oscillation (MJO) and the Pacific Decagonal Oscillation (PDO) in Papua (East Indonesia). This study uses an empirical approach with statistical calculations based on the PDO variable in the form of the PDO index, the amplitude variable which represents the MJO data and the rainfall for the province of Papua. Data for these two variables were obtained from NOAA and BoM, as well as rainfall data obtained from NASA. The data period analyzed was 40 years from 1981 to 2020. Two dates were filtered and correlations were analyzed using a simple linear regression method. The results of this research show that PDO is associated with MJO in Papua. This is clearly seen from the results of the correlation of the two phenomena. In addition, these two phenomena also affect the increase or decrease in rainfall in Papua. The second impact of this phenomenon on Papua (eastern part of the archipelago) is caused by the circulation of sea water from the Pacific Ocean through the Indonesian Toughflow.